2004
DOI: 10.1002/eji.200324400
|View full text |Cite
|
Sign up to set email alerts
|

The RhoA‐ and CDC42‐specific exchange factor Dbs promotes expansion of immature thymocytes and deletion of double‐positive and single‐positive thymocytes

Abstract: Specific members of the Rho family of GTPases exert unique influences on thymocyte proliferation, differentiation and deletion. Dbs is a guanine nucleotide exchange factor which is expressed throughout thymocyte development and is able to activate the Rho family GTPases CDC42, RhoA and RhoG. Transgenic mice expressing an activated form of Dbs had increased numbers of double-negative thymocytes. The Dbs transgene promoted expansion of double-negative thymocytes in the absence of pre-TCR, but had no effect on pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…DBS is a GEF for RHOA and CDC42, which is expressed throughout thymocyte development. Transgenic mice expressing an activated form of DBS had larger numbers of CD4 - CD8 - DN thymocytes, but increased apoptosis in later DP and SP thymocyte subsets55.…”
Section: Gtpases and Their Regulators In T Cellsmentioning
confidence: 94%
“…DBS is a GEF for RHOA and CDC42, which is expressed throughout thymocyte development. Transgenic mice expressing an activated form of DBS had larger numbers of CD4 - CD8 - DN thymocytes, but increased apoptosis in later DP and SP thymocyte subsets55.…”
Section: Gtpases and Their Regulators In T Cellsmentioning
confidence: 94%
“…The Dbl family members all possess two tandem conserved domains, the Dbl Homology (DH) and the Pleckstrin Homology (PH) domains (13-18). The DH domains of Dbl-GEFs are directly responsible for catalyzing GDP-GTP exchange activity while the PH domains are important for protein localization to the plasma membrane.…”
mentioning
confidence: 99%
“…Two families of GEFs have been discovered for Rho GTPases, which we here term the Dbl and Dock180 superfamilies . The Dbl family members all possess two tandem conserved domains, the Dbl homology (DH) and pleckstrin homology (PH) domains . The DH domains of Dbl-GEFs are directly responsible for catalyzing GDP−GTP exchange activity, while the PH domains are important for the localization of these proteins to the plasma membrane.…”
mentioning
confidence: 99%
“…A previous study has demonstrated that the DBS-130 inhibitors can reduce the motility of MDA-MB-231 cells in Transwell and scratch assays ( 48 , 49 ). DBS becomes activated and highly tumorigenic via truncation of the N-terminus, and the activation of DBS can promote cell proliferation during the development of hemocytes ( 50 ). However, the role of MCF2L/DBS in the drug resistance of tumor cells has not yet been studied.…”
Section: Discussionmentioning
confidence: 99%